2021
DOI: 10.33448/rsd-v10i14.21846
|View full text |Cite
|
Sign up to set email alerts
|

Plant extract as a strategy for the management of seed pathogens: a critical review

Abstract: Seeds associated to fungal pathogens are efficient vehicles for disease dissemination in the field. Such pathogens affect the seed quality and longevity, causing a decrease or loss of germination, discoloration, necrosis, and decay, in addition to leading to the production of mycotoxins in some pathosystems. To control them several synthetic chemicals are used. Nevertheless, the use of synthetic chemicals poses a risk to human health and the environment. Therefore, there is a growing demand for the use of alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…The methodology used in the research is a narrative literature review like those performed by Almeida et al (2021), Souza et al (2022) e Samreen et al (2021). The contents were observed in which the following search platforms were used: SciELO, ScienceDirect, Elsevier, PubMed, SpringerLink, Google Scholar, and CAPES Periodical.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The methodology used in the research is a narrative literature review like those performed by Almeida et al (2021), Souza et al (2022) e Samreen et al (2021). The contents were observed in which the following search platforms were used: SciELO, ScienceDirect, Elsevier, PubMed, SpringerLink, Google Scholar, and CAPES Periodical.…”
Section: Methodsmentioning
confidence: 99%
“…It is known that chemical control, especially the use of systemic fungicides, is the most used to control seed and plant diseases (Oerke 2006;Udayashankar et al 2012;Ranatunga 2013), but natural control methods or alternatives are also crucial in the control of these diseases, especially in terms of gaining space in the face of changes in public perceptions about the negative impacts of synthetic chemicals such as resistance gain, environmental damage and high cost (El-gali 2018;Silva et al 2019;Almeida et al 2021). From these disadvantages, antimicrobial characteristics have been sought in plants with intensified increase (Pushpavathi et al 2017).…”
Section: Natural Control Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…An analysis of scientific studies on the effectiveness of plant extracts against seed fungi of various crops showed 100 percent inhibition of phytopathogens, with most researchers using aqueous plant extracts (Almeida et al, 2021).…”
Section: Introductionmentioning
confidence: 99%